If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1z = my Solving x + -1z = my Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'z' to each side of the equation. x + -1z + z = my + z Combine like terms: -1z + z = 0 x + 0 = my + z x = my + z Simplifying x = my + z
| 18x+3=2x-48 | | 65047+6546= | | -8+4u=(-32) | | -4+90=50 | | x*6.25=800 | | (4x+1)=3x+7 | | 55=3u+13 | | 2x^2-49=x^2 | | x*0.0625=800 | | 3u-4=(-10) | | 6/7x-1/2x=5 | | 3u-4=10 | | 11+-p=6 | | 7x/8-3x/5=11/2 | | 57G+17=3 | | (8-i)-(-4-i)= | | 2/3x-5/9=-1 | | -14x-(-7)=35 | | 88=4y+8 | | 3(3x-1)=17 | | 2h+4=20 | | 1-(-m)=0 | | 7(4a-4)-1=14-8a | | -4f+-11=1 | | x^2+x-31=32-x | | 5x+250=600 | | 2x+15=-6x-20 | | 2(-6r-5)=-3(4r+2) | | 5x+6=(-19) | | Cos40=x/100 | | 5x+5(-5x+14)=-90 | | -3+4y=(-19) |